Homo-niewiadomo, stereotypy a rzeczywistość - Żółtkowski, Marcin (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2006)
The author arrives at an interesting conclusion. Why do gays actually need this famous right to adopt? What do the advocates get as they lie down in the ‘over my dead body’ gesture? The only outcome is a larger number of children in orphanages. More children will waste their lives (let us not forget that it is because of us heterosexuals). What about gays? Not to prevaricate one can say that instead of adopting children, they will get their own ones. This cannot be banned. Are we facing overwhelming hypocrisy then? When you refuse them the right to adopt, you are shouting „perverts, keep off children,” as you block the streets. Yet the world moves on walking along the sidewalk. Gays’ and lesbians’ children are born and are brought up by two fathers or mothers in turns, or at the same time. M³odzie¿ Wszechpolska (a nationalist, ultra-Catholic organization of Polish youth) is sleeping soundly having performed its duty, while a new generation is quietly growing up next door. Lonely children are crying in orphanages but M³odzie¿ Wszechpolska is enjoying an untroubled sleep. It has defended children against ‘perverts’and ‘fags’: those people from a different planet. They do not know any gay. Or at least, no gay who has come out...
Homo- or hetero-sexual, stereotypes versus reality